Antirheumatic therapy is associated with reduced complement activation in rheumatoid arthritis - Nguyen, Thao H. P.; Hokstad, Ingrid; Fagerland, Morten Wang; Mollnes, Tom Eirik; Hollan, Ivana; Feinberg, Mark W.; Hjeltnes, Gunnbjørg; Eilertsen, Gro Ø.; Mikkelsen, Knut; Agewall, Stefan (PloS one, 2022)
The complement system plays an important role in pathophysiology of cardiovascular disease (CVD), and might be involved in accelerated atherogenesis in rheumatoid arthritis (RA). The role of complement activation in response to treatment, and in development of premature CVD in RA, is limited. Therefore, we examined the effects of methotrexate (MTX) and tumor necrosis factor inhibitors (TNFi) on complement activation using soluble terminal complement complex (TCC) levels in RA; and assessed associations between TCC and inflammatory and cardiovascular biomarkers. We assessed 64 RA patients starting with MTX monotherapy (n = 34) or TNFi with or without MTX co-medication (TNFi±MTX, n = 30). ELISA was used to measure TCC in EDTA plasma. The patients were examined at baseline, after 6 weeks and 6 months of treatment. Median TCC was 1.10 CAU/mL, and 57 (89%) patients had TCC above the estimated upper reference limit (<0.70). Compared to baseline, TCC levels were significantly lower at 6-week visit (0.85 CAU/mL, p<0.0001), without significant differences between the two treatment regimens. Notably, sustained reduction in TCC was only achieved after 6 months on TNFi±MTX (0.80 CAU/mL, p = 0.006). Reductions in TCC after treatment were related to decreased C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and interleukin 6, and increased levels of total, high and low-density lipoprotein cholesterol. Similarly, baseline TCC was significantly related to baseline CRP, ESR and interleukin 6. Patients with endothelial dysfunction had higher baseline TCC than those without (median 1.4 versus 1.0 CAU/mL, p = 0.023). Patients with active RA had elevated TCC, indicating increased complement activation. TCC decreased with antirheumatic treatment already after 6 weeks. However, only treatment with TNFi±MTX led to sustained reduction in TCC during the 6-month follow-up period. RA patients with endothelial dysfunction had higher baseline TCC compared to those without, possibly reflecting involvement of complement in the atherosclerotic process in RA.